2015
DOI: 10.1039/c5ra15497a
|View full text |Cite
|
Sign up to set email alerts
|

Zeolitic imidazolate metal organic framework ZIF-8 with ultra-high adsorption capacity bound tetracycline in aqueous solution

Abstract: Synthetic process of ZIF-8 and a mechanism of tetracycline bound to ZIF-8 due to electrostatic attraction and π–π stacking interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(81 citation statements)
references
References 46 publications
6
73
0
2
Order By: Relevance
“…In particular, metal-organic frameworks (MOFs) are known to contain extremely small pores of nanometer scale, 16 exhibit well-ordered porous structures and chemical functionalities, have large specic surface areas, high pore volumes, adjustability of pore channels and offer directional modication of functional groups. [17][18][19] All of these characteristics suggest that MOFs are potential materials for cleaning phosphoruscontaminated water. Liu et al successfully prepared La-MOFs which could adsorb phosphate from aqueous solution, but a large amount of organic solvent (DMF) was used in the synthesis method, which is very unfriendly to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, metal-organic frameworks (MOFs) are known to contain extremely small pores of nanometer scale, 16 exhibit well-ordered porous structures and chemical functionalities, have large specic surface areas, high pore volumes, adjustability of pore channels and offer directional modication of functional groups. [17][18][19] All of these characteristics suggest that MOFs are potential materials for cleaning phosphoruscontaminated water. Liu et al successfully prepared La-MOFs which could adsorb phosphate from aqueous solution, but a large amount of organic solvent (DMF) was used in the synthesis method, which is very unfriendly to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the Langmuir model could better represent the TC adsorption process. The adsorption of TC onto MOF-818 was dominated by monolayer adsorption and chemical adsorption might play the main role in the process of TC adsorption [44].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…In comparison, MOFs have chemical and thermal stability, ease of structural functionalization, large specific surface area, and high porosity. More importantly, the pore sizes can be controlled and affinities toward pollute molecules including coordination bond, π-π interactions, hydrogen bonding and electrostatic interactions can also be designed on purpose [42][43][44][45]. Therefore, MOFs have been identified as one of the most efficient adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Sung Hwa Jhung et al [30] used ZIF-8 for the phthalic acid adsorption. Xiong et al [31] showed that ZIF-8 has ultra-high tetracycline adsorption capacity. Furthermore, fast adsorption and removal of benzotriazole by ZIF-8 was reported by Xiu-Ping Yan et al [32].…”
Section: Introductionmentioning
confidence: 99%